Predictors of obstructive sleep apnea in patients with chronic obstructive pulmonary disease - Safy Zahid Kaddah; Yousef Mohamed Amin Soliman; Heba Mousa; Naglaa Moustafa; Eman Kamal Ibrahim (The Egyptian Journal of Bronchology, 2023)
Abstract Background The co-existence of chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) is known as overlap syndrome, and both conditions share common risk factors and are associated with co-morbidities and poor outcomes. Methodology Sixty stable COPD patients were included in the study. We assessed body measurements, pulmonary functions to diagnose and assess COPD severity, arterial blood gases, STOB-BANG questionnaire (SBQ), Epworth sleepiness scale (ESS), and polysomnography (PSG) for diagnosis and classification of OSA severity. The aim of the study is to assess predictors of OSA among COPD patients. Results The prevalence of overlap syndrome was 70% among studied stable COPD patients, with a male-to-female ratio of 2:1, and SBQ and ESS were statistically higher in overlap syndrome with p values < 0.001 and 0.002, respectively. Oxygen desaturation index (ODI) was 42.72 ± 30.02 for overlap in comparison to 13.18 ± 5.80 for COPD with a significant p value of < 0.001, and T90 was significantly increased in the overlap group (26.75 ± 10.37) than the COPD-only group (1.8 ± 0.98, p value ≤ 0.001). We found a direct correlation between the GOLD stage and severity of OSA in overlap syndrome. The best cutoff value for the detection of overlap syndrome was ESS = 9 (sensitivity = 88.6% and specificity = 62.5%) and SBQ = 5 (sensitivity = 63.6% and specificity = 93.8%). Conclusion Overlap syndrome represents 70% of stable COPD patients. A direct relation was found between the GOLD stage and OSA severity in overlap syndrome. ESS and SBQ can be used for screening for OSA in COPD patients but with a lower cutoff value than those used for the general population. Trial registration Retrospectively registered, registration number is NCT05605431, date of registration October 29, 2022.